Plant Cadmium Resistance 2 (SaPCR2) Facilitates Cadmium Efflux in the Roots of Hyperaccumulator Sedum alfredii Hance - Lin, Jiayu; Gao, Xiaoyu; Zhao, Jianqi; Zhang, Jie; Chen, Shaoning; Lu, Lingli (Frontiers in Plant Science, 2020)
Hyperaccumulators are the preferred materials for phytoremediation. Sedum alfredii Hance is a cadmium (Cd) hyperaccumulator plant in China, although its detoxification mechanism remains unresolved. In our study, we cloned a gene belonging to the plant cadmium resistance (PCR) family, named SaPCR2, from the hyperaccumulating ecotype (HE) of S. alfredii. Sequence analysis indicated that SaPCR2 contained a cysteine-rich domain highly conserved in the PCR family and played an important role in Cd detoxification. Based on the relative quantitative results, SaPCR2 was highly expressed in the roots of HE S. alfredii, but not the shoots and Cd exposure did not significantly affect SaPCR2 expression. In contrast, the expression level of SaPCR2 was very low in plants of its non-hyperaccumulating ecotype (NHE). The subcellular localization of tobacco leaves showed that SaPCR2 was located to the plasma membrane and the expression of the SaPCR2 protein in a Zn/Cd-sensitive yeast Δzrc1 significantly increased its tolerance to Cd stress by decreasing the Cd content in cells. Heterologous expression of SaPCR2 in plants of both Arabidopsis thaliana and NHE S. alfredii significantly reduced the Cd levels in the roots, but not in the shoots. These results suggest that the overexpression of SaPCR2 in plants provides a route for Cd leak out of the root cells and protects the root cells against phytotoxicity of Cd stress. To the best of our knowledge, this is the first study of transporter-mediated root efflux of Cd in hyperaccumulator S. alfredii.